‘AMRITHAPALA’ (Janakia arayalpatra, Joseph & Chandrasekharan), A NEW DRUG FROM THE KANI TRIBE OF KERALA - P.PUSHPANGADAN; A. RAJASEKHARAN; P.K. RATHEESHKUMAR; C.R. JAWAHAR; K. RADHAKRISHNAN; C.P.R. NAIR; L. SARADA AMMA AND A.V. BHATT (Ancient Science Life, 1990)
Amrithapala (Janakia arayalpatra), a rare and endemic plant species found in the Southern forests of Western Ghat region of kerala, is used by the local ‘Kani’ tribe as an effective remedy for peptic ulcer, cancer-like afflictions and as a rejuvenating tonic. Search made in Ayurvedic literature indicates that the plant may be the divine drug named variously as MRITHA SANJEEVINI (the drug that can revive unconscious or dead) or SANJEEVINI, THAMPRA RASAYANI in the Oushadha Nighantu (Dictionary of Medicinal Drugs) of Tayyil Kumaran Krishnan (1906)